2006
DOI: 10.1073/pnas.0606032103
|View full text |Cite
|
Sign up to set email alerts
|

Multiple intermediates in SNARE-induced membrane fusion

Abstract: Membrane fusion in eukaryotic cells is thought to be mediated by a highly conserved family of proteins called SNAREs (soluble N-ethyl maleimide sensitive-factor attachment protein receptors). The vesicle-associated v-SNARE engages with its partner t-SNAREs on the target membrane to form a coiled coil that bridges two membranes and facilitates fusion. As demonstrated by recent findings on the hemifusion state, identifying intermediates of membrane fusion can help unveil the underlying fusion mechanism. Observat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

9
259
1

Year Published

2007
2007
2022
2022

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 212 publications
(269 citation statements)
references
References 39 publications
9
259
1
Order By: Relevance
“…A hemifusion intermediate was also detected at the single-liposome level by monitoring FRET between membrane-bound fluorophores in single fusion events between pairs of SNARE-reconstituted liposomes (7), and in flipped SNARE-mediated cell-cell fusion (8). These results suggest that the SNARE-dependent fusion of intracellular membranes like yeast vacuoles might also proceed through a hemifusion intermediate.…”
Section: Discussionmentioning
confidence: 71%
“…A hemifusion intermediate was also detected at the single-liposome level by monitoring FRET between membrane-bound fluorophores in single fusion events between pairs of SNARE-reconstituted liposomes (7), and in flipped SNARE-mediated cell-cell fusion (8). These results suggest that the SNARE-dependent fusion of intracellular membranes like yeast vacuoles might also proceed through a hemifusion intermediate.…”
Section: Discussionmentioning
confidence: 71%
“…For example, in the case of synaptic transmission, the reaction is tightly regulated by a number of proteins of which the SNAREs [soluble N-ethylmaleimide sensitive factor (NSF) attachment protein receptors] have been shown to play a crucial role (1)(2)(3). In vitro studies have demonstrated the sufficiency of SNAREs to mediate fusion when reconstituted into a number of model systems, including freestanding lipid vesicles (4-7), supported lipid bilayers (8)(9)(10), and tethered vesicles (11). Generally these studies suggest that SNAREs are able to bring two membranes into close apposition by forming a trans complex in a docking reaction which is highly energetically favorable (12).…”
mentioning
confidence: 99%
“…When tethering ligands such as biotin (21)(22)(23)(24) or a DNA oligonucleotide (11,12,25) are displayed on the supported bilayer, then individual intact vesicles displaying the complementary receptor can be held close to the surface where they can be visualized. Biotin-streptavidin tethers have been used extensively to isolate individual vesicles primarily in the context of single-molecule fluorescence measurements (21,24). In our experience, such tethered vesicles are relatively immobile on the surface, which is ideal for single-molecule measurements but less useful for probing interactions between tethered vesicles.…”
mentioning
confidence: 99%